Microstructure and microhardness of Al – Si alloy doped by Mg, Mn, Fe, Ni, Cu at high-speed solidification - Gusakova, Olga V.; Shepelevich, Vasily G. (Journal of the Belarusian State University. Physics, 2024)
The influence of high-speed solidification on the microstructure, grain structure, texture and microhardness of Al – Si system alloys doped by metals has been studied. It is shown that, with a constant elemental composition in thickness, the foil has a layered microstructure, which is formed as a result of various solidification conditions. It has been established that in the foil layer adjacent to the crystalliser, solidification proceeds with the formation of nanosized particles of two types: globular silicon particles with an average size of 110 nm and non-globular particles containing metals with a size of up to 30 nm. The reasons of increasing the microhardness of the alloy due to additional braking of gliding dislocations on incoherent particles according to the Orowan mechanism are analysed depending on the volume fraction of silicon. The possibility of increasing the microhardness of silumin alloyed with metals to 2 GPa has been noted, which is 4 times higher than the microhardness of cast silumin obtained during quasi-equilibrium solidification. The developed alloys are promising starting materials for powder metallurgy in the manufacture of pressed products.